(untitled) (Journal of the College of Basic Education, 2026)
This study seeks to analyze the grammatical phenomena in the hadiths of the Prophet Muhammad, and to reveal the implications they contain in light of Arabic grammar and its precise approach. The study was based on the opinion of the trend that permits citing the noble hadith on the condition that the authenticity of the word narrated from the Prophet is proven, which prompted the adoption of Sahih Imam Muslim bin Al-Hajjaj Al-Naysaburi as a field of application; Because of its proven narration and sound text.. The research was titled: Grammatical significance in Arabized nouns - applied models from Sahih Muslim).. The structure of the research required dividing it into an introduction, two topics, and a conclusion. I ask God Almighty to make this effort sincere for His sake. If I succeed, it is from His grace and success. If I fall short, it is sufficient for me that I have done my best and had good intentions.